2020
DOI: 10.1111/myc.13195
|View full text |Cite
|
Sign up to set email alerts
|

Molecular epidemiology and phylogenetic analyses of environmental and clinical isolates of Cryptococcus gattii sensu lato in Taiwan

Abstract: Background The rare occurrence of cryptococcosis caused by Cryptococcus gattii sensu lato (C. gattii s.l.) leads to the difficulties in studying the molecular epidemiology of this globally emerging disease. Objectives To establish the molecular epidemiological profile of C. gattii s.l. in Taiwan, and understand the genetic relationship between locally endemic and global isolates. Methods A nationwide survey on environmental C. gattii s.l. in Taiwan was conducted from 2017 to 2019. The geographic distribution a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
13
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(15 citation statements)
references
References 53 publications
2
13
0
Order By: Relevance
“…Among the other VGI strains, we identified one strain of ST106, one of the most virulent strains in the invertebrate model, Galleria mellonella 28 , and the dominant ST in Taiwan. It was also isolated in Singapore, Malaysia and the USA 30 . Another ST, ST56, the most represented in this study among the VGIs, was previously described in Brazil and Italy 31 .…”
Section: Discussionsupporting
confidence: 61%
“…Among the other VGI strains, we identified one strain of ST106, one of the most virulent strains in the invertebrate model, Galleria mellonella 28 , and the dominant ST in Taiwan. It was also isolated in Singapore, Malaysia and the USA 30 . Another ST, ST56, the most represented in this study among the VGIs, was previously described in Brazil and Italy 31 .…”
Section: Discussionsupporting
confidence: 61%
“…In this study, around 10% of CM cases were caused by C. gattii during 2000–2010 and 2013–2020 at KCGMH. Lin et al reported that, although no environmental C. gattii isolates were found in Pingtung, ST630 was commonly identified in Kaohsiung [ 19 ]. However, no ST630 clinical isolates were found in Taiwan, according to Lin et al and the current study.…”
Section: Discussionmentioning
confidence: 99%
“…In the last few decades, several widely used molecular methods have been used worldwide to determine the genotypes of clinical, environmental, and veterinary isolates of the members of the C. neoformans and C. gattii species complexes to investigate their geographical distribution, molecular epidemiology, and population genetics [ 19 , 20 , 21 , 22 , 23 ]. Understanding the epidemiological and microbiological characteristics of local Cryptococcus strains and clinical features of CM is essential for the development of efficient diagnosis and treatment strategies.…”
Section: Introductionmentioning
confidence: 99%
“…Members of the currently delineated genus Cryptococcus inhabit temperate forests worldwide (Chowdhary et al, 2012; Cogliati et al, 2016; Kidd et al, 2007; Lin et al, 2021). Non‐pathogenic Cryptococcus species are rare and only known from a very few isolates of plant‐insect origin, including C. amylolentus , C. wingfieldii , and C. floricola (Passer et al, 2019).…”
Section: Model Yeast Genera In Temperate Forestsmentioning
confidence: 99%